1999
DOI: 10.1210/jc.84.2.743
|View full text |Cite
|
Sign up to set email alerts
|

Human Peripheral Blood Mononuclear Cells Express Gonadotropin-Releasing Hormone (GnRH), GnRH Receptor, and Interleukin-2 Receptor  -Chain Messenger Ribonucleic Acids That Are Regulated by GnRH in Vitro

Abstract: The hypothalamic decapeptide, GnRH, plays a critical role in human reproduction. In addition to the well known effects of GnRH on pituitary cells, there is evidence supporting the presence of GnRH-binding sites in tissues other than pituitary cells, including lymphocytes. In addition, a GnRH-like substance has been found to be secreted from lymphoid cells. However, the precise nature of GnRH secretion and binding in immune cells has not been fully established. In this study, we used the RT-PCR method to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
2
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 0 publications
8
99
2
3
Order By: Relevance
“…In 1980, it was shown that macrophages and lymphocytes were able to produce adrenocorticotropin and endorphins (Blalock and Smith, 1980;Smith and Blalock, 1981). To date, immune cells produce around 30 neuroendocrine mediators, including growth hormone (Weigent et al, 1988), prolactin (Montgomery et al, 1987), proenkephalin A (Rosen et al, 1989), somatostatin (Fuller and Verity, 1989;, oxytocin-vasopressin (Geenen et al, 1987), atrial natriuretic peptide (Vollmar et al, 1992), substance P (Ho et al, 1997;Lai et al, 1998;Lambrecht et al, 1999), gonadotropin-releasing hormone (Chen et al, 1999), glucocorticoids (Lechner et al, 2000), procalcitonin (Oberhoffer et al, 1999), corticotropin-releasing factor (CRF) (Brouxhon et al, 1998), vasoactive intestinal peptide (VIP; see Section II. ), pituitary adenylate cyclase-activating polypeptide (PACAP) , neuropeptide Y (Schwarz et al, 1994), calcitonin gene-related peptide (CGRP) (Singaram et al, 1991), ␣-melanocyte-stimulating hormone (␣MSH) (Lolait et al, 1986;Rajora et al, 1996), and opioid peptides (Przewlocki et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In 1980, it was shown that macrophages and lymphocytes were able to produce adrenocorticotropin and endorphins (Blalock and Smith, 1980;Smith and Blalock, 1981). To date, immune cells produce around 30 neuroendocrine mediators, including growth hormone (Weigent et al, 1988), prolactin (Montgomery et al, 1987), proenkephalin A (Rosen et al, 1989), somatostatin (Fuller and Verity, 1989;, oxytocin-vasopressin (Geenen et al, 1987), atrial natriuretic peptide (Vollmar et al, 1992), substance P (Ho et al, 1997;Lai et al, 1998;Lambrecht et al, 1999), gonadotropin-releasing hormone (Chen et al, 1999), glucocorticoids (Lechner et al, 2000), procalcitonin (Oberhoffer et al, 1999), corticotropin-releasing factor (CRF) (Brouxhon et al, 1998), vasoactive intestinal peptide (VIP; see Section II. ), pituitary adenylate cyclase-activating polypeptide (PACAP) , neuropeptide Y (Schwarz et al, 1994), calcitonin gene-related peptide (CGRP) (Singaram et al, 1991), ␣-melanocyte-stimulating hormone (␣MSH) (Lolait et al, 1986;Rajora et al, 1996), and opioid peptides (Przewlocki et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The finding of GnRH-I mRNA and peptide expression in red drum lymphocytes appears to be consistent with GnRH-I mRNA expression in tissues of the mammalian immune system, such as lymphocytes, thymocytes, thymus, and spleen (Azad et al 1991a,b 1993, Maier et al 1992, Chen et al 1999. In addition, both GnRH-I and GnRH-II are expressed in human T cells (Chen et al 2002).…”
Section: Discussionmentioning
confidence: 53%
“…GnRH-I expression has been reported also in a variety of mammalian non-neural tissues such as bone marrow, gastric smooth muscle cells, gonads, heart, incisors, kidney, liver, pancreas, placenta, prostate, and skeletal muscle (Dolan et al 2003, Chen et al 2004, Tiong et al 2004. In addition, GnRH-I expression and GnRH binding sites have been demonstrated in different tissues of the immune system of mammals (Chen et al 1999). Similarly in teleosts, GnRH-I expression has been shown in gill, gonad, heart, kidney, liver, muscle, pituitary, and spleen (Ferriere et al 2001, Mohamed et al 2005.…”
Section: Introductionmentioning
confidence: 96%
“…The q(rt-PCR) was performed by using AccuPower® Greenstar™ qPCR PreMix reagent kit (Bioneer, Korea) and Exicycler™ 96 Real-Time Quantitative Thermal Block (Bioneer, Korea), according to method described by Chen HF [22]. The SYBER Green I based q(rt-PCR) premix reagent kit is designed for PCR amplification of cDNA for target gene by using LH-r primer and housekeeping gene (GAPDH).…”
Section: Performed Of Q (Realtime-pcr)mentioning
confidence: 99%